Effect of dapsone alone and in combination with intracellular antibiotics against the biofilm form of B. burgdorferi - Richard I. Horowitz; Krithika Murali; Gauri Gaur; Phyllis R. Freeman; Eva Sapi (BMC Research Notes, 2020)
Abstract Objective Lyme disease is a tick-borne, multisystemic disease caused by Borrelia burgdorferi. Standard treatments for early Lyme disease include short courses of oral antibiotics but relapses often occur after discontinuation of treatment. Several studies have suggested that ongoing symptoms may be due to a highly antibiotic resistant form of B. burgdorferi called biofilms. Our recent clinical study reported the successful use of an intracellular mycobacterium persister drug used in treating leprosy, diaminodiphenyl sulfone (dapsone), in combination therapy for the treatment of Lyme disease. In this in vitro study, we evaluated the effectiveness of dapsone individually and in combination with cefuroxime and/or other antibiotics with intracellular activity including doxycycline, rifampin, and azithromycin against Borrelia biofilm forms utilizing crystal violet biofilm mass, and dimethyl methylene blue glycosaminoglycan assays combined with Live/Dead fluorescent microscopy analyses. Results Dapsone, alone or in various combinations with doxycycline, rifampin and azithromycin produced a significant reduction in the mass and protective glycosaminoglycan layer and overall viability of B. burgdorferi biofilm forms. This in vitro study strongly suggests that dapsone combination therapy could represent a novel and effective treatment option against the biofilm form of B. burgdorferi.